Electron microscopic findings suggestive of focal and segmental glomerulosclerosis in patients with steroid-resistant nephrotic syndrome. (2nd January 2019) - Nili, Fatemeh; Saboori, Fatemeh; Jahanzad, Issa; Mehrazma, Mitra
ABSTRACT: Distinction between minimal change disease and unsampled Focal Segmental Glomerulosclerosis is a challenging concept in kidney biopsy of patients with nephrotic syndrome with minimal histopathological findings. This study was performed to compare electron microscopic findings in patients with steroid-resistant nephrotic syndrome with minimal histopathological abnormalities and cases with Focal Segmental Glomerulosclerosis. This Cohort study was conducted in Cancer Institute, Imam Khomeini Hospital Complex, Tehran, Iran. Twenty patients with steroid-resistant nephrotic syndrome and minimal changes on the light microscopic study were selected as case group. Similarly, 20 patients with Focal Segmental Glomerulosclerosis were selected as the control group. Ultrastructural findings were re-evaluated and scored qualitatively (0–3+). In patients with minimal changes on light microscopic evaluation, clinical course of the disease was followed after 5 years. Mean ages of the patients (8 women and 12 men) in case and control groups were 12.9 and 15.9 years, respectively ( p > 0.05). There was no significant difference in number of examined glomeruli and sampling from cortico–medullary junction area between the groups. The mean percentage of sclerotic glomeruli in control group was 15.4%. Tubular atrophy and interstitial fibrosis were more frequent in control patients. Podocyte proliferation, GBM duplication (involving more than 10% of capillary walls), and moderate to severe multifocal expansion of mesangial matrix were significantly more obvious in FSGS patient samples ( p < 0.05). No statistically significant difference was found in severity of cytoplasmic vacuolization, GBM wrinkling and splitting between the groups. Most of (80%) the patients with minimal changes improved during the 5-year follow-up. Generally, we concluded that Podocyte proliferation, GBM remodeling, and moderate to severe mesangial matrix expansion are the most reliable findings on electron microscopic examination in favor of FSGS.